2006
DOI: 10.1063/1.2140286
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo phase diagram for diblock copolymer melts

Abstract: A partial phase diagram is constructed for diblock copolymer melts using lattice-based Monte Carlo simulations. This is done by locating the order-disorder transition (ODT) with the aid of a recently proposed order parameter and identifying the ordered phase over a wide range of copolymer compositions (0.2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 54 publications
4
40
0
2
Order By: Relevance
“…This results in complex finite size artefacts. Nevertheless, phase diagrams have been obtained in recent years [337][338][339]. Particle-based and field-based simulations have provided evidence that for symmetrical diblock copolymers ( f = 1/2), the transition to the lamellar phase is shifted [224,340], compared to the mean-field phase diagram, and becomes first order [340][341][342], in agreement with the theoretical expectation [116] (see Section 3.…”
Section: Copolymer Systemssupporting
confidence: 74%
See 2 more Smart Citations
“…This results in complex finite size artefacts. Nevertheless, phase diagrams have been obtained in recent years [337][338][339]. Particle-based and field-based simulations have provided evidence that for symmetrical diblock copolymers ( f = 1/2), the transition to the lamellar phase is shifted [224,340], compared to the mean-field phase diagram, and becomes first order [340][341][342], in agreement with the theoretical expectation [116] (see Section 3.…”
Section: Copolymer Systemssupporting
confidence: 74%
“…Two examples of phase diagrams obtained with different simulation methods are shown in Figure 3.8: One was calculated by Matsen et al [338] using Monte Carlo simulations of copolymers with length N = 30 in a simple lattice model (left), and one by Lennon et al [342] using field-theoretical calculations (right) at Ginzburg parameter C = 50. Both phase diagrams significantly improve on the SCF phase diagram of Figure 3.5 (right) in the weak segregation regime, and reproduce the main qualitative features of the experimental phase diagram (Figure 3.5, left): The transitions are first order everywhere.…”
Section: 25)mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, those simulations [12] show a direct transition from disordered phase to C and G nanophases like in experiment [19] and particle Monte Carlo simulation [28,29], but unlike the SCFT phase diagram [9].…”
Section: A-b-b Melts Can Self-assemble Inmentioning
confidence: 74%
“…In the study of diblock copolymer melts, Matsen et al also observed a hysteresis loop between the cooling and heating energy curves. [50,51] Figure 16 shows the typical temperature dependence of the heat capacity C v for the confined systems, as well as for the bulk one. We can clearly see that there are two peaks in each C v curve.…”
Section: The Variation Of Morphologies and Chainmentioning
confidence: 99%